Oil Droplet Impact Dynamics in Aero-Engine Bearing Chambers-Correlations Derived from Direct Numerical Simulations. - Peduto, Davide (Forschungsberichte Aus Dem Institut Für Thermische Strömungsmaschinen Ser., 2015)
Annotation